Coping and sleep quality in youth: An Experience Sampling study. Issue 3 (17th January 2023) - Hagemann, Noëmi; Kirtley, Olivia J.; Lafit, Ginette; Vancampfort, Davy; Wampers, Martien; Decoster, Jeroen; Derom, Catherine; Gülöksüz, Sinan; De Hert, Marc; Jacobs, Nele; Menne‐Lothmann, Claudia; Rutten, Bart P. F.; et al.
Abstract: Introduction: Sleep quality is closely linked with mental health. Two factors that influence sleep are coping style and locus of control, yet these have not been investigated in daily life. In this study, we examined associations between coping styles and sleep quality in daily life and the potential mediating effect of daily locus of control in a sample of youth, a group particularly vulnerable to developing psychopathology. Methods: Three hundred and seventy‐nine youths from the TwinssCan study participated in an Experience Sampling study, assessing sleep quality as well as state locus of control over the most negative event from the previous day. Participants also completed the Utrecht Coping List, which assessed engagement, disengagement, and emotion‐focused coping. Results: Disengagement, "passive reaction, " and emotion‐focused coping were associated with lower daily sleep quality. State locus of control did not mediate any effects of coping styles on quality of sleep. Conclusions: Disengagement, "passive reaction, " and emotion‐focused coping were associated with decreased sleep quality during several consecutive days, which may put youths at risk for developing future insomnia, and strain their mental well‐being over time. Thus, there may be value in asking about coping when a young individual presents with sleep problems; however, impaired coping when sleeping poorly should also be considered.